Research Trends of Digital Literacy in English Language Learning: a Systematic Literature Review - Mahendra, Jonanda Wahyu; Maghfiroh, Ana; Harmanto, Bambang; Sudirman, Rio (Edulib, 2024)
With the rise of digital literacy today, many educators use it to improve and hone their students' abilities in digital technology-based literacy. This study employs the Systematic Literature Review method and used the Dimensions software to search for data using keywords. The collected scientific articles are then analyzed to answer the research question: What are the research issues and themes in digital literacy research and how is English learning through digital literacy?